A novel artificial film of lithiophilic polyethersulfone for inhibiting lithium dendrite. (20th January 2022) - Zhuang, Dongmei; Huang, Xianli; Chen, Zhihui; Wu, Haowen; Sheng, Lei; Zhao, Manman; Bai, Yaozong; Liu, Gaojun; Xue, Hairong; Wang, Tao; Chen, Yonggang; He, Jianping
Research highlights: PES is first time used to modify the li electrode which shows excellent lithium affinity. PES film with polar functional groups ( O  =  S  =  O ) can realize the redistribution of the lithium ion flow and a uniform nano-columnar lithium layer can be obtained even in the high current density of 5 mA cm −2 . (3) the PES film prolongs the half-cell life three times than control group with higher coulombic efficiency. ABSTRACT: The dendrite problem and low Coulombic efficiency of lithium anode have hindered its commercial application for long time. In this paper, the Polyethersulfone (PES) film is spin-coated to construct a composite lithium anode. With the polar functional groups of PES, the lithiophilicity of the anode is greatly improved. Non-conductive uniform structure with polar functional groups ( O  =  S  =  O ) constructed on the lithium metal anode can realize the redistribution of the lithium ion flow and reduce the probability of dendrite formation in the "hot spot" area. A uniform nano-columnar lithium layer can be obtained even in the high current density of 5 mA cm −2 . Electrochemical interface studies have illustrated that PES film can increase the migration speed of lithium ion among the electrodes, increase the reduction reaction rate of lithium ion. Finite element simulation calculations show that the PES film can effectively reduce the concentration of lithium ion near the dendrite tip. In addition, with the Cu-PES structure modified by 3.3 mg mL −1 PES, the average Coulombic efficiency of half-cell reaches 90%, and the cell can run for 220 cycles stably which is three times than control group in 0.5 mA cm −2 . Graphical abstract: Image, graphical abstract